Functional Characterization of Novel ATP7B Variants for Diagnosis of Wilson Disease - Guttmann, Sarah; Bernick, Friedrich; Naorniakowska, Magdalena; Michgehl, Ulf; Groba, Sara Reinartz; Socha, Piotr; Zibert, Andree; Schmidt, Hartmut H. (Frontiers in Pediatrics, 2018)
Background: Diagnosis of rare Wilson disease (WD) in pediatric patients is difficult, in particular when hepatic manifestation is absent. Genetic analysis of ATP7B represents the single major determinant of the diagnostic scoring system in WD children having mild symptoms. Objectives: To assess the impact of molecularly expressed ATP7B gene products in order to assist diagnosis of Wilson disease in pediatric patients having a novel mutation and subtle neuropsychiatric disease. Methods: The medical history, clinical presentation, biochemical parameters, and the genetic analysis of ATP7B were determined. Due to ambiguous clinical and biochemical findings and identification of a novel compound ATP7B mutation with unknown disease-causing status, a molecular analysis of the ATP7B gene products in a previously well characterized cell model was performed. Results: The ATP7B variants were transgenically expressed and the respective gene function molecularly characterized. Despite normal mRNA expression, low ATP7B protein expression of the mutants p.L168P and p.S1423N was observed (34.3 ± 8% and 66.0 ± 8%, respectively). Copper exposure did not result in decreased viability of transgenic cells as compared to wild type. Intracellular copper accumulation was reduced (≤47.9 ± 8%) and intracellular protein trafficking was impaired. Conclusion: Our report suggests that functional characterization of novel ATP7B mutants can assist diagnosis; however mild functional impairments of ATP7B variants may hamper the value of such approaches.